2022
DOI: 10.1108/wje-03-2022-0102
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of variable thickness longitudinal fin with functionally graded material in dry and fully wet conditions

Abstract: Purpose When the temperature of an air conditioning unit’s fin surface goes below its dew point temperature, condensation forms on the unit’s surface. As a result, the cooling coil’s performance is compromised. By altering the cross-section and heat conductivity of the fins, the performance of such systems can be improved. This study aims to analyze the thermal performance of longitudinal fins made up of a variable thickness (assuming constant weight) and functionally graded material. Design/methodology/appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Yontar et al (2020) have reported the numerical solution of constant thickness annular fin using a joint approach. Bajpai et al (2022) investigated the performance of varying geometry FGM longitudinal fins for fully wet conditions. Ranjan and Mallick (2018) reported the performance analysis of FGM annular fin based upon multiple variable thermal parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yontar et al (2020) have reported the numerical solution of constant thickness annular fin using a joint approach. Bajpai et al (2022) investigated the performance of varying geometry FGM longitudinal fins for fully wet conditions. Ranjan and Mallick (2018) reported the performance analysis of FGM annular fin based upon multiple variable thermal parameters.…”
Section: Introductionmentioning
confidence: 99%
“…(2020) have reported the numerical solution of constant thickness annular fin using a joint approach. Bajpai et al. (2022) investigated the performance of varying geometry FGM longitudinal fins for fully wet conditions.…”
Section: Introductionmentioning
confidence: 99%